ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI PERTUMBUHAN EKONOMI DI RIAU 2018-2021 - Dwiky Irsyad Fadilah; Winny Perwithosuci (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2023)
Economic growth is one of the indicators to assess the state of a country's economy and is a benchmark for assessing the success of development. However, several resource problems differ in each region, namely the Human Development Index, poverty, responsiveness, income inequality, and government spending as factors that trigger the regional economy. This study analyzes the relationship between the human development index, poverty, reactions, income inequality, and government spending with economic growth. The research aims to identify the effect of these factors on economic growth in Riau Province in 2018-2021. This current research employs panel data regression analysis. The model selected in the regression panel data is the Fixed Effect Model (FEM). The results of the t-test stated that government spending had a positive effect on GRDP, while sluggishness and responsiveness had a negative effect on GRDP. Meanwhile, HDI and income inequality did not affect Regency/City GRDP in Riau Province in 2018-2021.